POTENSI GEOWISATA DI KABUPATEN PASER, KALIMANTAN TIMUR - Desianto Payung Battu; Ikhwanur Adha; Teddy Kurniawan; Hamriani Ryka; Maulana Ichsan Eriyanto (Sekolah Tinggi Teknologi MIGAS, 2023)
Paser Regency is one of the regencies in East Kalimantan which is located in the southernmost part. This district has unique natural conditions and has the potential to become a tourist attraction. Geomorphologically, Paser Regency has various conditions from coastal areas to hilly and mountainous areas. Paser Regency also has geological conditions that vary from Pre-Tertiary to Quaternary age. The purpose of this study is to introduce to the public, both domestically and abroad, geotourism locations in Paser Regency and to examine its geotourism potential. Data was collected using descriptive methods, namely field observations including descriptions, recordings, and measurements to determine the geological and tourist conditions at the research site. Petrological analysis was carried out to determine the type and composition of rocks in detail and was carried out to provide information on the lithological characteristics as edu-geotourism materials at that location. The analysis produces a geotourism map that shows geotourism location information. Paser Regency has 9 locations that have the potential as geotourism objects, namely Lempesu Waterfall, Boga Mountain, Losan Cave, Tengkorak Cave, Loyang Cave, Rambutan Mountain Waterfall, Embung Muru, Doyam Seriam Waterfall, and Danum Layong Hot Spring. Increasing the location of geotourism needs to be done, both in infrastructure development and sustainable management, so that tourists can be comfortable in enjoying their visit.